2000
DOI: 10.1021/ja000182x
|View full text |Cite
|
Sign up to set email alerts
|

A New Mechanism of Action Proposed for Ramoplanin

Abstract: Ramoplanin (Figure 1) is a cyclic glycolipodepsipeptide antibiotic that kills gram positive bacteria by inhibiting cell wall biosynthesis. Ramoplanin was shown to block the conversion of Lipid I to Lipid II, 1 a reaction that is catalyzed by the intracellular GlcNAc transferase, MurG (Scheme 1). It was proposed that ramoplanin inhibits MurG by complexing Lipid I, which prevents it from being utilized as a substrate. Below we show that ramoplanin also inhibits the polymerization of Lipid II; therefore, we propo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
96
0
1

Year Published

2001
2001
2009
2009

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 91 publications
(101 citation statements)
references
References 15 publications
(21 reference statements)
4
96
0
1
Order By: Relevance
“…Walker's verification of transglycosylase (TGase) inhibition by ramoplanin in vivo suggests that the primary mechanism of bacterial killing involves Lipid II sequestration (15). However, ramoplanin differs from transglycosylase inhibitors such as moenomycin and mersacidin in that it not only inhibits TGase activity, but also generates a metabolic block at the level of the MurG reaction, forcing a buildup of cellular pools of Lipid I (12,13).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Walker's verification of transglycosylase (TGase) inhibition by ramoplanin in vivo suggests that the primary mechanism of bacterial killing involves Lipid II sequestration (15). However, ramoplanin differs from transglycosylase inhibitors such as moenomycin and mersacidin in that it not only inhibits TGase activity, but also generates a metabolic block at the level of the MurG reaction, forcing a buildup of cellular pools of Lipid I (12,13).…”
Section: Resultsmentioning
confidence: 99%
“…Brotz and coworkers demonstrated that ramoplanin altered the chromatographic migration profiles of both Lipid I and Lipid II, suggesting that the two form a complex with the antibiotic, thereby raising the possibility that ramoplanin might also interfere with transglycosylation via capture of Lipid II (1). Using citronellyl-Lipid II, a soluble synthetic analogue of Lipid II, Walker and coworkers (15) subsequently confirmed that ramoplanin indeed possessed this second PG biosynthesis inhibitory activity by directly showing its inhibition of extracellular transglycosylase activity. Importantly, it was also shown that on complexation with citronellyl-Lipid II, ramoplanin underwent a ligand-induced aggregation to produce insoluble fibrils, precluding molecular characterization of the inhibitory complex.…”
mentioning
confidence: 95%
“…Lipid I analogue 9 was prepared as described in Men et al (9) and Ye et al (10) and enzymatically converted to lipid II analogue 10 by using E. coli MurG as described in Lo et al (11).…”
Section: Methodsmentioning
confidence: 99%
“…Lipid II sequestration precludes formation of the mature, fully cross-linked peptidoglycan, leading to a mechanically weakened cell wall and bacterial death from osmotic lysis (11)(12)(13)(14). Thus, like the glycopeptide antibiotics, ramoplanin inhibits cell wall biosynthesis, but the molecular underpinnings are distinct, since the binding epitopes on Lipid II that are recognized by the two types of antibiotics are largely non-overlapping (3,4,10,15,16).…”
mentioning
confidence: 99%
“…Determining the stoichiometry with which Lipid II binds ramoplanin has been complicated. Early circular dichroism titrations suggested a 1:1 stoichiometry (14). However, this value was subsequently revised after analysis of the effects of ramoplanin on the conversion of heptaprenyl Lipid I to heptaprenyl Lipid II by the transglycosylase/transpeptidase PBP1b; these experiments led to an estimate of a 2:1 stoichiometry for the ramoplanin:Lipid II complex (17).…”
mentioning
confidence: 99%